2007
DOI: 10.1080/02678290601104817
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic properties of symmetrical and asymmetrical triphenylene homologues possessing fluoroalkylated side chains

Abstract: Two types of homologues (symmetrical and asymmetrical in rotational symmetry) of novel triphenylene compounds possessing fluoroalkyl and alkyl side chains were synthesized via an alternative method. X-ray diffraction and DSC measurements showed that these homologues are thermotropic liquid crystals with a hexagonal columnar (Col h ) mesophase. The phase transition temperatures (Col h -Iso) for both symmetrical and asymmetrical fluoroalkyloxytriphenylenes increase to about 180uC, and are independent of fluorome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In addition, Shimizu et al have reported a series of triphenylene derivatives with six fluorinated ether chains (HexaFTPDLCs), which showed hexagonal columnar (Col h ) mesophases (29)(30)(31)(32). Comparing with corresponding hexaalkoxytriphenylenes, Shimizu's HexaFTPDLCs have more stable columnar mesophases and higher melting points.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, Shimizu et al have reported a series of triphenylene derivatives with six fluorinated ether chains (HexaFTPDLCs), which showed hexagonal columnar (Col h ) mesophases (29)(30)(31)(32). Comparing with corresponding hexaalkoxytriphenylenes, Shimizu's HexaFTPDLCs have more stable columnar mesophases and higher melting points.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, increasing fluoromethylene chain length increases the order of Col h mesophase. Terasawa et al [20] reported symmetrical and unsymmetrical triphenylenes with three fluoroalkyl chains and three alkyl chains, and these triphenylenes show more stable Col h mesophase than both fluorinated triphenylenes and non-fluorinated triphenylenes. The results imply that the fluorophilic-fluorophobic effect plays a significant role in the thermal stability of Col mesophase.…”
Section: Introductionmentioning
confidence: 97%
“…Triphenylene DLCs have been extensively studied as one-dimensional conductors [9] , photoconductors [10] , light-emitting diodes [11] , gas sensors, and LC displays [13] . Triphenylenes with different lengths of soft chains, both hydrophilic and hydrophobic peripheral chains [14,15] , hydrogen bonding substituents [16] , perfluorinated chains showing fluorophilic and fluorophobic effect [17][18][19][20][21] , metallic substituents [22] and polymerizable functional groups [23,24] have been exploited. More recently, discotic liquid crystals with fluorinated chains have been investigated to enhance the stability of columnar phase and charge carrier mobility [25] .…”
Section: Introductionmentioning
confidence: 99%
“…The phase transition temperatures (Col h -I) for all the symmetrical and asymmetrical fluoroalkyloxytriphenylenes increase to c. 180uC, in comparison with fluoroalkyloxytriphenylenes possessing six fluoroalkyl side chains, and alkyloxytriphenylenes; these transition temperatures are independent of fluoromethylene chain length and the rotation symmetry of the chemical structure. All the symmetrical and asymmetrical fluoroalkyloxytriphenylenes possessing three fluoroalkyl side chains are thermally stabilized, compared with fluoroalkyloxytriphenylenes possessing six fluoroalkyl side chains (F1-F6) and alkyloxytriphenylenes (H1-H6) [18].…”
Section: Introductionmentioning
confidence: 99%